AI-Generated False Media and Trust in the Media - Khym, Siena (Advances in Social Sciences Research Journal, 2026)
Media deceit spreads through social media, mainstream news, and published articles. Artificial intelligence and misinformation can now convincingly mimic reality through technology. This blurs the line between fact and fiction, threatening to divide society. Misinformation influences voting behavior on education, healthcare, and the economy. The study examines the impact of realistic false media on media trust when individuals must distinguish between AI-generated and human-authored texts. I believe AI-generated writing and identification will harm journalism. Thirty-two participants, aged 13 to 80, were surveyed in four sections after demographic inquiries. Initially, participants identified AI-generated and human-authored materials. In the second session, participants distinguished between human-authored texts and AI-generated texts. They were asked if human and AI articles represented the same event. A follow-up questionnaire examined the erosion of faith in the media. It’s hypothesized that the participants will be more skeptical of the media after exposure to AI-generated text. Media skepticism will likely increase with age, particularly among individuals who have difficulty recognizing AI-generated content. Deceptive media erodes faith in journalism by impairing individuals’ ability to discern fact from fiction. As media credibility erodes, individuals are increasingly forced to make high-stakes judgments based on unreliable information, accelerating social polarization.